Business Development Strategy at Hallacoffee Bandung - Iqbal Al Fikri Rachman; Fanji Wijaya; Erna Herlinawati; Dadan Abdul Aziz Mubarok (Dinasti Publisher, 2024)
In Indonesia, especially in the city of Bandung, the existence of coffee shops requires Hallacoffee to maintain its consistency and presence so that it can compete with other coffee shops in the city of Bandung. It is interesting to study this research by applying the SWOT analysis model, we can maximize the potential and advantages that Hallacoffee has in maintaining its company. The aim of this research is to design a design-oriented innovation strategy for Hallacoffee by formulating a strategy to help generate the opportunities needed for Hallacoffee. The research methodology used is qualitative research using descriptive techniques. The data collection process involves two methods: secondary data and primary data. Secondary data is obtained from sources such as papers, the internet and journals. Primary data was obtained through documentation, observation and direct interviews conducted with Hallacoffee owners and customers. Designing the IFE Matrix, EFE Matrix, and QSPM Matrix are used to design business strategies to identify several opportunities, threats, strengths and weaknesses as key factors in developing the business. Hallacoffee has a high level of proficiency in the fields of management and planning. Hallacoffee has the potential to compete with other coffee shops, especially in the city of Bandung. The need in the current conditions is to adopt and firm expansion strategy.